PSTPIP2 Inhibits the Inflammatory Response and Proliferation of Fibroblast-Like Synoviocytes in vitro - Yao, Yao; Yu, Haixia; Liu, Yaru; Xu, Qingqing; Li, Xiaofeng; Meng, Xiaoming; Huang, Cheng; Li, Jun (Frontiers in Pharmacology, 2018)
Abstract Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease and its pathogenesis remains unclear. Fibroblast-like synoviocytes (FLSs) play an important role in the pathogenesis of RA. Proline-serine-threonine phosphatase interacting protein 2 (PSTPIP2) is an adaptor protein, which is associated with auto-inflammatory disease. In this study, we selected adjuvant-induced arthritis (AIA) as animal model to study the role of PSTPIP2 in FLSs. We found that the expression of PSTPIP2 was significantly down-regulated in synovial tissues and FLSs of AIA rat compared with normal group. And overexpression of PSTPIP2 could inhibit the proliferation and inflammatory response of FLSs. Moreover, the proliferation and inflammatory response of FLSs were promoted with PSTPIP2 silencing treatment. In terms of mechanism, we found that the expression of PSTPIP2 was closely related to NF-κB signaling pathway. Overall, our results suggested that PSTPIP2 inhibits the proliferation and inflammatory response of FLSs and it is might closely related to NF-κB signaling pathway in FLSs of AIA rat.